The brain and nervous system - Ward, Brian R. (London ; New York : F. Watts, 1981)
Describes the structure and functions of the brain and spinal cord and how neurons carry messages to and from the brain.
Includes index.
Keywords: Brain -- Juvenile literature; Nervous system -- Juvenile literature; Brain; Nervous system